Social learning in games: Stimulating institutional and behavior change in relation to water use in India - Falk, Thomas; Meinzen-Dick, Ruth S.; Priyadarshini, Pratiti; Singh, Subrata; Mittal, Rajesh (2021)
Prepared by: Thomas Falk, Ruth Meinzen-Dick Pratiti Priyadarshini, Subrata Singh, Rajesh Mittal